(3cJGH GdYdd hGdCYQGV dLGdjfhSs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd dLGdjfhS (B: (3Ef Chd eG jfHZi dfG Cf fPcQg eGdfSF GdPi fSejg eQVkG s
(3BNQgG (B:s
(3hCeG CfG adTabJi ddhbJ HGdJWhjd bO QCjJ Cf CbWY GdcdGe gfG s
(3eQJH Ydi SJg ebGdGJ s
(3h HYV ChQGbgG eWehSI GdJQJjHs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
Keywords: (3GdWHs